2015
DOI: 10.1002/bjs.10046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delay between imaging and treatment in patients with potentially curable pancreatic cancer

Abstract: Operation within 32 days of diagnostic imaging reduced the risk of tumour progression to unresectable disease by half compared with a longer waiting time. The results of this study highlight the importance of efficient clinical PDAC management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
2
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 31 publications
5
64
2
6
Order By: Relevance
“…Despite a decreasing trend in non-resection at surgical exploration, the magnitude is still worrying. Although a Swedish study 26 suggested that treatment delay was associated with a higher probability of finding unresectable disease, delay in the Netherlands seems relatively short (median 28 versus 42 days respectively) 27 . Furthermore, neoadjuvant treatment (such as FOLFIRINOX -folinic acid, fluoro uracil, irinotecan, oxaliplatin), which could hamper correct preoperative staging 28 , but also increases resection rates 29,30 , was essentially not used in the present study period.…”
Section: Discussionmentioning
confidence: 97%
“…Despite a decreasing trend in non-resection at surgical exploration, the magnitude is still worrying. Although a Swedish study 26 suggested that treatment delay was associated with a higher probability of finding unresectable disease, delay in the Netherlands seems relatively short (median 28 versus 42 days respectively) 27 . Furthermore, neoadjuvant treatment (such as FOLFIRINOX -folinic acid, fluoro uracil, irinotecan, oxaliplatin), which could hamper correct preoperative staging 28 , but also increases resection rates 29,30 , was essentially not used in the present study period.…”
Section: Discussionmentioning
confidence: 97%
“…One study demonstrated that the resection rate was significantly higher when the imaging-to-resection interval was 32 days or less, when compared to longer waiting times (87 versus 74%). 22 Another recent study described that the implementation of a fast track pathway without preoperative biliary drainage for periampullary malignancies leads to a significant reduction in time from index CT to surgery, when compared to those who had been stented before referral (16 versus 65 days). In this study, the resection rate of the group without preoperative biliary drainage was significantly higher, when compared to that of the not drained group (97 versus 75%).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies claimed however that a detrimental effect on the prognosis could be introduced if certain waiting time threshold was exceeded. For example, prolonged interval between diagnostic imaging and resection over 32 days for pancreatic cancer was associated with significantly increased risk of unexpected tumor progress as determined at laparotomy [21]. A recent population-based study [22] emphasized a significantly lower overall survival among patients with non-metastatic invasive breast cancer after 30 days waiting time for surgery (approximately 10% decreasing survival for every 30-day increment in waiting).…”
Section: Discussionmentioning
confidence: 99%